Purchase decision patterns of non-bank sharia housing in Bandar Lampung City during Covid-19: Price exploration and digital marketing - Khavid Normasyhuri; Siti Nurohmah (Journal of Islamic Economics Lariba, 2023)
IntroductionThe housing sector, including sharia housing, has been affected by Covid-19. Many studies have analyzed the impact of Covid-19 on the sharia housing industry, but research focusing on non-bank financing is still limited. ObjectivesThis study aims to analyze how consumer purchasing decisions for housing during Covid-19 are influenced by price and digital marketing. MethodThis study can be categorized as quantitative study by collecting data from 500 consumers selected through purposive sampling in the Bandar Lampung City. The obtained data was then analyzed using SmartPLS software. ResultsThe result shows that price and digital marketing have significant impact on consumers’ purchase decision of non-bank Sharia housing during Covid-19. ImplicationsSharia housing developers should effectively utilize digital marketing content and pricing strategy to attract potential consumers in Bandar Lampung City.Originality/NoveltyThis study highlights unique pricing and digital marketing strategies by Sharia housing developers during Covid-19. This study is also unique for its approach to non-bank Sharia housing as mode of financing.